2006
DOI: 10.1007/s10803-006-0248-1
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour Management Problems as Predictors of Psychotropic Medication and Use of Psychiatric Services in Adults with Autism

Abstract: This study examines a group of synaesthetes who report colour sensations in response to music and other sounds. Experiment 1 shows that synaesthetes choose more precise colours and are more internally consistent in their choice of colours given a set of sounds of varying pitch, timbre and composition (single notes or dyads) relative to a group of controls. In spite of this difference, both controls and synaesthetes appear to use the same heuristics for matching between auditory and visual domains (e.g., pitch … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 40 publications
3
38
1
Order By: Relevance
“…Lunsky et al (2009) compared patients with ASD and ID to other individuals accessing tertiary level mental healthcare in Ontario and found that individuals with ASD and ID were younger, spent more days in hospitals, and were less likely to have a psychotic disorder diagnosis than both patients with and without ID. Interestingly, fewer than half of the individuals with ASD and ID had an additional psychiatric diagnosis, although almost all (91%) were prescribed psychotropic medication, which is consistent with previous studies (Tsakanikos et al 2006(Tsakanikos et al , 2007a. Tsakanikos et al (2007b) reported that behavioral management problems predicted psychotropic medication and use of psychiatric services in adults with pervasive developmental disorder and ID.…”
Section: Mental Health Servicessupporting
confidence: 88%
“…Lunsky et al (2009) compared patients with ASD and ID to other individuals accessing tertiary level mental healthcare in Ontario and found that individuals with ASD and ID were younger, spent more days in hospitals, and were less likely to have a psychotic disorder diagnosis than both patients with and without ID. Interestingly, fewer than half of the individuals with ASD and ID had an additional psychiatric diagnosis, although almost all (91%) were prescribed psychotropic medication, which is consistent with previous studies (Tsakanikos et al 2006(Tsakanikos et al , 2007a. Tsakanikos et al (2007b) reported that behavioral management problems predicted psychotropic medication and use of psychiatric services in adults with pervasive developmental disorder and ID.…”
Section: Mental Health Servicessupporting
confidence: 88%
“…This is because high-profile problems such as aggression or self-injury tend to draw clinical attention away from less dramatic internalizing ones, especially when informants provide a substantial portion of the information about symptoms (Cantwell, 1996; Carlson, & Kashani, 1988; Rutter, 1998). The presence of disruptive and aggressive behaviors has been found to have an impact on prescribing patterns (Stolker, Heerdink, Leufkins, Clerkx, & Nolen, 2001; Tsakanikos, Costello, Holt, Sturmey, & Bouras, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Among the general population, these outcomes can include adolescent and adult antisocial behavior, conduct problems, substance use, and depression (Fite et al 2008;Lochman and Wayland 1994;Zahn-Waxler et al 2005). Among individuals with developmental disabilities, aggression is one of the strongest predictors of crisis intervention re-referrals (Shoham-Vardi et al 1996), admission and readmission to residential facilities (Lakin 1983), use of psychotropic medication (Stone et al 1989;Tsakanikos et al 2007), and overall quality of life (Gardner and Moffatt 1990).…”
Section: Significance Of the Problemmentioning
confidence: 99%